2000
DOI: 10.1207/s15506878jobem4403_10
|View full text |Cite
|
Sign up to set email alerts
|

Gender-Differentiated Production Features in Toy Commercials

Abstract: Chandler, D., Griffiths, M. (2000). Gender-Differentiated Production Features in Toy Commercials. Journal of Broadcasting & Electronic Media, 44 (3), 503-520.Twenty years ago researchers found that quite apart from the manifest content of television commercials aimed at children, certain formal features showed a marked tendency to vary according to the sex of the target consumers: in particular certain post-production features (transitions and voice-overs). The current study involved a content analysis of form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0
3

Year Published

2002
2002
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 11 publications
2
10
0
3
Order By: Relevance
“…Our results are consistent with content analyses on the depiction of sex-role stereotypes in commercials, which have often found that advertisers use highly stereotypical means to attract the attention of boys and girls (Allan and Coltrane, 1996;Browne, 1998;Chandler and Griffiths, 2000). Some of these researchers have raised the concern that television advertising imposes or reinforces traditional gender stereotypes.…”
Section: Appeals In Different Product Categoriessupporting
confidence: 90%
See 2 more Smart Citations
“…Our results are consistent with content analyses on the depiction of sex-role stereotypes in commercials, which have often found that advertisers use highly stereotypical means to attract the attention of boys and girls (Allan and Coltrane, 1996;Browne, 1998;Chandler and Griffiths, 2000). Some of these researchers have raised the concern that television advertising imposes or reinforces traditional gender stereotypes.…”
Section: Appeals In Different Product Categoriessupporting
confidence: 90%
“…One method derives the age and gender of the target audiBrought to you by | Radboud University Nijmegen Authenticated Download Date | 2/1/15 12:07 PM ence from the key characters in the commercial (e. g., Welch, HustonStein, Wright, and Plehal, 1979;Winick et al, 1973). The other method is based on the coder's estimation of the target audience (e. g., Chandler and Griffiths, 2000). In this latter method, the coders consider both the nature of the advertised product and the gender and age of the key characters in the commercial.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…As expected, advertisements with male central figures appeared significantly more active than those with female central figures. These results are in agreement with previous findings (Chandler and Griffiths, 2000;Macklin and Kolbe, 1984;Vema, 1975;Welch et al, 1979). As expected, ads with male central figures contained also more aggression behaviors than those with female central figures.…”
Section: Discussionsupporting
confidence: 93%
“…Approximately one-fourth of the commercials include cannot code (19.8%) and mixed (6.6%) characters, reflecting the high proportion of dismembered characters or inter-age groupings; the former may be emblematic of production features in toy commercials which favor shorter and rapid shots, pacing, and transitions (Chandler and Griffiths 2000).…”
Section: Resultsmentioning
confidence: 99%